2004
DOI: 10.1128/iai.72.11.6318-6323.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Calixarenes Enhance Innate Defense Mechanisms in Murine Macrophages and Induce Control ofMycobacterium tuberculosisInfection in Mice

Abstract: Tuberculosis remains the leading cause of death among infectious diseases, accounting for more than two million deaths annually. The incidence of the disease is increasing globally, partially because of the resurgence of drug-resistant strains of Mycobacterium tuberculosis. Calixarenes are macrocyclic oligomers, some of which are able to modify the growth of M. tuberculosis in infected cells. Most experimental work has been carried out with Macrocyclon, also known as HOC 12.5EO. In this study, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The proximity of these quite different ligating units, reinforces the binding within supramolecular partners by exploiting synergistic and solvation-desolvation effects. 31 The binding mode shown by the Vancomycin mimic calixarene ligands, able to address a single amino acid (or a very limited number of amino acids) in a large biopolymer could be systematically classified as "single point" recognition ( Figure 5b), a way of binding very recently elegantly exploited by Crowley and Hof to recognize a protein mutated on single positions upon methylation of the Lysine residues (vide infra). Vancomycin is, in fact, a natural antibiotic whose activity is linked to its ability to selectively recognize the terminal L-Lys-D-Ala-D-Ala sequence of peptidoglycan, one of the main cell wall constituents in Gram-positive bacteria.…”
Section: Hybrid Charactermentioning
confidence: 99%
“…The proximity of these quite different ligating units, reinforces the binding within supramolecular partners by exploiting synergistic and solvation-desolvation effects. 31 The binding mode shown by the Vancomycin mimic calixarene ligands, able to address a single amino acid (or a very limited number of amino acids) in a large biopolymer could be systematically classified as "single point" recognition ( Figure 5b), a way of binding very recently elegantly exploited by Crowley and Hof to recognize a protein mutated on single positions upon methylation of the Lysine residues (vide infra). Vancomycin is, in fact, a natural antibiotic whose activity is linked to its ability to selectively recognize the terminal L-Lys-D-Ala-D-Ala sequence of peptidoglycan, one of the main cell wall constituents in Gram-positive bacteria.…”
Section: Hybrid Charactermentioning
confidence: 99%
“…Calixarenes are able to modify its growth and macrocyclon is effective in controlling its infections. Colston et al [42] revealed that macrocyclons (Fig. 5) were effective in athymic and they synthesized a number of structurally related calixarenes expressing significant antimycobacterial activity.…”
Section: Anti-mycobacterial and Anti-proliferativitymentioning
confidence: 98%
“…In a later paper, D'Arcy Hart and colleagues revisited these compounds and compared Macrocyclon, with an average of 12.5 -CH 2 CH 2 O-repeat units and terminating in a hydroxy group, with 'HOC-60', 67, an analogue with 60 repeat units [47]. At this point, it was also appreciated that the compounds were calix[8]rather than calix [4] [48]. In these later experiments, both macrophages and live mice were infected with M. tuberculosis and the range of calixarenes, 68 to 72 (Figure 13), increased.…”
Section: Macrocyclonmentioning
confidence: 99%